2018
DOI: 10.1371/journal.pone.0191460
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of night-time and weekend admissions on in-hospital mortality in acute myocardial infarction patients in Japan

Abstract: BackgroundPatients admitted to hospital during off-hours may experience poorer quality of care and clinical outcomes. However, few studies have examined the variations in clinical processes and outcomes across admission times and days of the week in acute myocardial infarction (AMI) patients. This study aimed to comparatively analyze the effect of weekend and weekday admissions stratified by admission time on in-hospital mortality in AMI patients.Methods and resultsUsing a large nationwide administrative datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
0
11
1
Order By: Relevance
“…[11] There are studies about effect of night times and weekend admission on morbidity and mortality. [12,13]. However, we could not find effect of prolonged hospital stay on over all morbidity and mortality.…”
Section: Discussioncontrasting
confidence: 63%
“…[11] There are studies about effect of night times and weekend admission on morbidity and mortality. [12,13]. However, we could not find effect of prolonged hospital stay on over all morbidity and mortality.…”
Section: Discussioncontrasting
confidence: 63%
“…AMI occurs when the blood supply to the heart is decreased (ischemia) for an extended period which acts as a chief contributor to global disease burden (Gong et al, ; Mizuno, Kunisawa, Sasaki, Fushimi, & Imanaka, ). Although the pathophysiology of AMI has been largely advanced by reperfusion and drug therapies, adverse left ventricular remodeling after AMI is still the commonest reason of heart failure (Sun, Xie, Du, Sun, & Liu, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the design of our study is unable to provide an explanation for the potential causes underlying the observed association between day of admission and mortality, we can speculate that longer time from symptom onset to diagnosis and treatment and hospital understaffing during weekend might play a role. 18 The theory of understaffing was recently questioned by two recent articles by Aldridge et al 19 and Hsu et al 20 : these authors were unable to demonstrate a correlation between weekend staffing and mortality risk in relation to the day of admission and concluded that further investigation would have been necessary before adopting a 7day service as a solution to the weekend effect.…”
Section: Jcm-d-18-00220mentioning
confidence: 99%